ANALISIS KEANDALAN STRUKTUR DAN KONSEP ARSITEKTUR PADA BANGUNAN BERTINGKAT - Endah Harisun; Imran Imran (Journal of Science and Engineering, 2018)
The design of a building requires various stages of calculation that consider many aspects so that the results that are in accordance with its functions are not only seen from structural aspects but also economic and aesthetic aspects are also taken into consideration. In building planning, the aesthetic and architectural development in it often leads to irregular / asymmetrical forms of buildings which then cause problems with building seismic irregularities.The building of the Universitas Khairun Postgraduate must be a strong, sturdy educational building and has an attractive and formal architectural appearance. Therefore researchers are interested in examining the structure of the building.The approach in this study is to use a qualitative and quantitative research approach. both approaches are used together or combined, where the approach is used interchangeably. In the first stage using a qualitative approach, so that the architectural concept of building Postgraduate was found. Furthermore, the structure of the building was tested by quantitative methods using the Sap 2000 program.The purpose of this study is to compile the analysis of structural and architectural concepts in the Building of the Universitas Khairun Postgraduate. The building of the Universitas Khairun Postgraduate must be a strong, sturdy educational building and has an attractive and formal architectural appearance.Angus J. Macdonald (2001). Struktur & Arsitektur. Jakarta: Erlangga.Badan Meteorologi dan Geofisika propinsi Jawa Barat.Jimmy S. Juwana (2004). Panduan Sistem Bangunan Tinggi. Jakarta: Erlangga.Hale N. Tongren dan james P. Thompson (2000:32)Neufert, Ernst (1996). Data Arsitek Jilid 1, Trans Sunarto Tjahjadi, Jakarta : Erlangga.Neufert, Ernst (2002). Data Arsitek Jilid 2, Trans Sunarto Tjahjadi dan Ferryanto Chaidir, Jakarta : Erlangga.Schodek, Daniel L. (1983). Struktur. Bandung: Pt ErescoWanita   S.A,   Silabus   Metoda   Perancangan   Arsitektur   II.   Unikom Bandung.Wikipedia Pameran (http://id.wikipedia.org/wiki/Pameran,   diakses  pada  tanggal  15  maret 2010)Wikipedia Bandung (http://id.wikipedia.org/wiki/Bandung_diakses  pada   tanggal   05  April 2010)http://www.archistructures.org (diakses pada tanggal 15 Juli 2018)http://www.arcspace.com (diakses pada tanggal 15 Juli 2018)http://id.w3dictionary.org/index.php?q=exhibition hall (diakses pada tanggal 15 Juli 2018)http://www.singaporeexpo.com. (diakses pada tanggal 17 Juli 2018)Wikipedia Hamburg Airport  (http://en.wikipedia.org/wiki/Hamburg_Airport, diakses  pada tanggal  5Juli 2018)